1993
DOI: 10.1177/0022343393030001006
|View full text |Cite
|
Sign up to set email alerts
|

Children and Adolescents' Conceptions of Peace, War, and Strategies to Attain Peace: A Dutch Case Study

Abstract: This article examines age-related changes in the conceptions children and adolescents hold about peace, war, and strategies to attain peace. These were expected to change from concrete, materially related to abstract, norm-related conceptions. The conceptions were assessed by means of a semi-structured questionnaire presented to 101 Dutch children between 8 and 16 years of age and divided into five age groups (mean ages 8, 10, 12, 14, and 16 years). Each age group consisted of approximately equal numbers of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
2
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 13 publications
6
80
2
1
Order By: Relevance
“…Miljević-Ridički & LugomerArmano, 1994) girls have tended to be less supportive (and less knowledgeable) of war compared to boys. However it has also been suggested that they tend to grasp the concept of peace earlier and conceptualise it in a more sophisticated way than boys (Hakvoort & Oppenheimer, 1993 with academic researchers -how easy will it be for them to articulate their concerns about war and peace from within the classroom? This alone is clearly a matter for further research work.…”
Section: Discussionmentioning
confidence: 99%
“…Miljević-Ridički & LugomerArmano, 1994) girls have tended to be less supportive (and less knowledgeable) of war compared to boys. However it has also been suggested that they tend to grasp the concept of peace earlier and conceptualise it in a more sophisticated way than boys (Hakvoort & Oppenheimer, 1993 with academic researchers -how easy will it be for them to articulate their concerns about war and peace from within the classroom? This alone is clearly a matter for further research work.…”
Section: Discussionmentioning
confidence: 99%
“…Studies about the perception of war report similar findings regarding gender. Male students tend to be more interested in the incidents of conflict and war than female students (Geddie & Hildreth, 1944;Tolley, 1973, cited in Hakvoort & Oppenheimer, 1993Frydenberg et al, 2001) and female students tend to regard interpersonal quarrels and disputes, things closer to them in social relations, as a war whereas male students see war as army and soldiers, things not so usual in their daily lives (Hakvoort & Oppenheimer, 1993). Teachers should be aware of the differences between male and female students' perspectives, guide male students into dialogue and negotiations, and try to reduce female students' anxiety and concerns by developing their skills of logical reasoning.…”
Section: Journal Of Qualitative Research In Education -Joqrementioning
confidence: 99%
“…Findings that have emerged regarding children's general understanding of peace and war show some similarities across studies, despite children's cultural differences and differences in exposure to political violence. For example, many children understand war in terms of its concrete details-the objects and activities of war (e.g., military weapons and fighting or killing) and peace as the absence of war or violence (Hakvoort and Oppenheimer 1993;Hakvoort and Hagglund 2001;McLernon and Cairns 2001;Myers-Bowman et al 2005;Oppenheimer and Kuipers 2003;Souza et al 2006;Walker et al 2003) or as the presence of prosocial behaviors such as being nice or sharing (Covell et al 1994;Hakvoort and Hagglund 2001;Myers-Bowman et al 2005;Walker et al 2003).…”
Section: Understanding Young Children's Conceptions Of War Peace Anmentioning
confidence: 99%
“…Romania, 5-6 years, peace only Cretu (1988) Sweden and The Netherlands, 7-17 years, peace and war Hakvoort and Hagglund (2001) The Netherlands, 8-16 years, peace and war Hakvoort and Oppenheimer (1993) US and Yugoslavia, 3-12 years, peace and war Myers-Bowman et al (2005) US, 3-12 years, peace and war Walker et al (2003) differently. They suggested interpersonal, prosocial behaviors (i.e., making friends) as a way to make peace when asked the more personal question.…”
Section: Understanding Young Children's Conceptions Of War Peace Anmentioning
confidence: 99%